2015
DOI: 10.9761/jasss2621
|View full text |Cite
|
Sign up to set email alerts
|

Matemati̇ğe İli̇şki̇n Akademi̇k Başari-Özyeterli̇li̇k Ve Tutum Arasindaki̇ İli̇şki̇leri̇n

Abstract: The aim of this study is to find out relationships between fifth grade students' academic achievement, attitudes and self-efficacy towards maths. Relational screening model was used as a qualitative research model. Data was gathered by "The Maths Attitude Scale" and "The Maths Self-efficacy Scale" which were developed by the researcher. Target population of the study was fifth graders studying in the centre of Çanakkale province. The sampling of the study comprises 1565 fifth grade students from 27 primary sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 13 publications
0
4
0
10
Order By: Relevance
“…In the literature, some studies emphasize that students' mathematics self-efficacy levels differ according to gender (Çakıroğlu & Işıksal, 2009;Öztürk & Şahin 2015;Pajares, 2005;Pajares & Graham, 1999) whereas others suggest that they do not differ according to gender (Akay & Boz, 2011;Pajares, 2005;Pajares & Graham, 1999;Yamaç, 2011). Studies on academic success emphasize that students' mathematics self-efficacy levels are a good indicator of their performance in mathematics (Malpass, O'Neil, & Hocevar, 1999;Pajares & Graham 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, some studies emphasize that students' mathematics self-efficacy levels differ according to gender (Çakıroğlu & Işıksal, 2009;Öztürk & Şahin 2015;Pajares, 2005;Pajares & Graham, 1999) whereas others suggest that they do not differ according to gender (Akay & Boz, 2011;Pajares, 2005;Pajares & Graham, 1999;Yamaç, 2011). Studies on academic success emphasize that students' mathematics self-efficacy levels are a good indicator of their performance in mathematics (Malpass, O'Neil, & Hocevar, 1999;Pajares & Graham 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Pajares ve Miller (1994) (Yağmur, 2012;Yenilmez & Kakmacı, 2008). Matematik öz yeterlik algısının sınıf düzeyine göre farklılaştığı fakat bu farklılığın üst sınıf seviyesindeki öğrencilerin lehine olduğunu ifade eden araştırmalar da mevcuttur (Çakıroğlu & Işıksal, 2009;Umay, 2001 (Çelik, 2012;Öztürk & Şahin, 2015;Pajares & Miller, 1994). Bu sonuçla çelişkili olan Gündoğdu (2013) Üstbilişsel farkındalık ve üstbiliş stratejilerin matematik başarısı ile ilişkisine yönelik çalışmalara bakıldığında; matematik başarısı ile üstbiliş stratejilerinin anlamlı bir ilişkiye sahip olduğu (Canca, 2005;Ekenel, 2005;Özsoy, 2007;Ektem, 2007;Çelik, 2012), üstbilişsel farkındalık düzeyi puanları ile matematik başarı puanları arasında ilişkinin var olduğu (Balcı, 2007) Öğrencilerin matematik başarıları ile matematik öz yeterlik algıları arasında pozitif yönde, orta düzeyde, anlamlı bir ilişki olduğu tespit edilmiştir.…”
Section: üStbilişsel Farkındalık Düzeyinin Farklılığıunclassified
“…Çünkü üstbilişsel farkındalık sahibi öğrenciler üst düzey düşünür, sorgular, bilgiye kendisi ulaşır. Literatür incelendiğinde de matematik başarısı ile üstbilişsel farkındalığın ilişkili olduğuna dair birçok çalışma yer almaktadır (Balcı, 2007;Canca, 2005;Çelik, 2012;Ektem, 2007 (Alcı, 2007;Çelik, 2012;Çağlayan, 2010;Duran, 2011;Gülten & Soytürk, 2013;Kitsantas, Cheema & Ware, 2011;Öztürk & Şahin, 2015;Pajares & Miller, 1994;Reçber, 2011;Şengül & Gülbağcı, 2013;Terzi & Mirasyedioğlu, 2009…”
Section: Introductionunclassified
“…The scores obtained from the sub-dimensions of mathematics self-efficacy indicated that the four dimensions explained about 61% of the total variance in mathematics achievement. When the relevant literature is examined, it can be seen that many studies (Alcı et al, 2010;Chen, 2003;Chen and Zimmerman, 2007;Güven and Cabakcor, 2012;Lopez, Lent, Brown and Gore, 1997;Öztürk and Şahin, 2015;Pajares and Kranzler, 1995;Usher, 2009;Üredi and Üredi, 2005;Williams and Williams, 2010) are consistent with this finding. Students' metacognitive skills and mathematics selfefficacy explained about 52% of the total variance in mathematics achievement.…”
Section: Discussionmentioning
confidence: 80%